INTEGRATING RISK MANAGEMENT INTO PROJECT SCHEDULING: A CRITICAL PATH METHOD APPROACH IN COAL MINING DEVELOPMENT PROJECT - Setiyawan, Bayu; Nursyamsiah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyses the integration of risk management into project scheduling in a coal mining development project. A mixed-methods case study was applied, combining interviews, observations, document analysis, and structured questionnaires. Project scheduling was conducted using the Critical Path Method (CPM), while risk assessment followed the AS/NZS 4360:2004 framework. The initial CPM analysis identified five activities on the critical path (A–B–D–E–F) with a total duration of 90 weeks. A risk assessment revealed thirteen potential risks, including two high-priority items, six moderate-to-high risks, four moderate risks, and three low risks. Control strategies such as avoidance, reduction, transfer, and acceptance were proposed to mitigate these risks. After incorporating risk management into the CPM schedule, the project duration extended to 94 weeks, reflecting additional preventive measures and contingency buffers. While the schedule lengthened, the revised plan provided greater resilience against disruptions and improved reliability for project execution. These findings indicate that integrating risk management into project scheduling produces a more realistic and achievable timeline, especially for large-scale and high-risk projects such as mining operations. Theoretically, this research contributes a framework for risk-adjusted scheduling by combining deterministic scheduling with proactive risk analysis. Practically, it offers project managers valuable guidance to minimize disruptions, enhance decision-making, and increase the probability of successful and timely project completion.